Reactor neutrinos in a gadolinium-loaded Super-Kamiokande - Goldsack, A (2022)
In July of 2020, Super-Kamiokande (SK), a 50 kt water Cherenkov detector, entered its new phase: SK-Gd [1]. In this phase, the detector’s once-ultrapure water was doped with 0.02% gadolinium sulphate octahydrate by mass, increased to 0.06% in July 2022. This provides far greater sensitivity to neutron captures, thereby increasing the detection efficiency of electron antineutrinos interacting via inverse beta decay. One such source of these neutrinos is the numerous fission products in nuclear reactor cores. To date, only one reactor neutrino interaction has been identified in a large scale water Cherenkov detector [2], in part due to their energy spectrum extending less than 10 MeV above the Cherenkov threshold of positrons in water. A search has been performed for reactor neutrinos in data obtained by SK’s Wideband Intelligent Trigger (WIT) system from December 2020 to October 2021, using a boosted decision tree-based selection method. The search intended to identify an increase in event rate consistent with that expected due to the restart of 9 Japanese reactor cores between December of 2020 and October of 2021. Apparent issues with the WIT data between March and August of 2021 motivated the comparison of the rates measured in the data before and after this period. Though the measured rate up to March 2021 of (1.6 ± 0.2) d−1 was consistent with predictions, the rate measured between August and October 2021 was found to be (8.8 ± 0.4) d−1, far in excess of the predicted rate of 3.7 d−1. While not inconsistent with the expected total interaction rate of 9.75 d−1, an unreasonably large signal efficiency would be required for this increase to be solely explained by reactor restarts. One suspected cause of this increase is the persistence of issues with the WIT data from March 2021, continuing after August, when the data was previously thought to be once again stable. As such, this work cannot conclusively say that reactor neutrinos have been identified in SK; however, the Monte Carlo studies presented in this thesis indicate that the experiment has this capability.